Survei Pembentukan Karakter Mahasiswa Selama Pembelajaran Daring : (Survey of Student Character Building During online Learning) - Ayu Wahyuni; Prima Nucifera (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
Since the epidemic of the corona virus, especially in Indonesia, it has had an impact and change in various aspects, including in the field of education, the implementation of an online learning system (in the network). This is a concern and a separate problem in the learning process. Because learning should be a complex activity which is an interaction between two directions in conveying or getting certain information and making changes for the better for students. The formation of the character of students is one of the main essence of the goals of national education. Therefore, it is necessary to conduct research on the effect of online learning on the formation of student character. This study aims to determine how the influence of online learning on the character formation of biology education students at one of the universities in Aceh Province. This type of research is descriptive qualitative research to reveal the character of students during online learning. The research subjects were students of the fifth semester of biology education wich amounts to 40 students. The results showed that even in an online learning atmosphere, the student's character for self-confidence, motivation, responsibility, effort, initiative, strong will, compassion, cooperation, critical thinking, problem solving ability and concentration on goals can be explored well, this is a reference that online learning is still able to explore the character of students so that national education goals can be achieved. Abstrak. Sejak mewabahnya virus corona terutama di Indonesia memberikan dampak dan perubahan dari berbagai aspek termasuk dalam bidang Pendidikan yang diberlakukannya sistem pembelajaran daring (dalam jaringan). Hal ini menjadi perhatian dan permasalahan tersendiri dalam proses pembelajaran. Karena seharusnya pembelajaran merupakan suatu kegiatan yang kompleks yang merupakan interaksi antara dua arah dalam menyampaikan atau mendapatkan informasi tertentu dan membuat perubahan kearah yang lebih baik bagi peserta didik. Pembentukan karakter peserta didik merupakan salah satu hakikat utama dari tujuan pendidikan Nasional. Oleh karena itu perlu dilakukan penelitian tentang pengaruh pembelajaran daring terhadap pembentukan karakter mahasiswa. Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh pembelajaran daring terhadap pembentukan karakter mahasiswa pendidikan biologi disalah satu Universitas di Provinsi Aceh. Jenis penelitian ini adalah penelitian deskriptif kualitatif untuk mengungkap karakter mahasiswa selama pembelajaran daring. Subjek penelitian adalah mahasiswa semester V pendidikan biologi yang berjumlah 40 0rang. Hasil penelitian menunjukkan bahwa meskipun dalam suasana pembelajaran daring karakter mahasiswa untuk percaya diri, motivasi, tanggung jawab, usaha, inisiatif, kemauan kuat, kasih sayang, kerjasama, berpikir kritis, kemampuan memecahkan masalah dan konsentrasi pada tujuan dapat tergali dengan baik.